Background Speech Effects on Sentence Processing during Reading: An Eye Movement Study - Hyona J; Ekholm M (PUBLIC LIBRARY SCIENCE, 2025)
Effects of background speech on reading were examined by playing aloud different types of background speech, while participants read long, syntactically complex and less complex sentences embedded in text. Readers' eye movement patterns were used to study online sentence comprehension. Effects of background speech were primarily seen in rereading time. In Experiment 1, foreign-language background speech did not disrupt sentence processing. Experiment 2 demonstrated robust disruption in reading as a result of semantically and syntactically anomalous scrambled background speech preserving normal sentence-like intonation. Scrambled speech that was constructed from the text to-be read did not disrupt reading more than scrambled speech constructed from a different, semantically unrelated text. Experiment 3 showed that scrambled speech exacerbated the syntactic complexity effect more than coherent background speech, which also interfered with reading. Experiment 4 demonstrated that both semantically and syntactically anomalous speech produced no more disruption in reading than semantically anomalous but syntactically correct background speech. The pattern of results is best explained by a semantic account that stresses the importance of similarity in semantic processing, but not similarity in semantic content, between the reading task and background speech.